2019
DOI: 10.1002/app.47803
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and nonisothermal crystallization properties of coal gasification fine slag glass bead‐filled polypropylene composites

Abstract: Coal gasification fine slag (CGFS) was subjected to calcination at 600 °C for 7 h, forming CGFS glass beads (CGFSGB). CGFSGB was successfully incorporated into polypropylene (PP) by melt compounding. The results indicated that CGFSGB has the potential to replace calcium carbonate in the plastics market. Thermogravimetric analysis showed obvious reinforcement in thermal stability by incorporation of CGFSGB, but crystallization ability decreased. The CGFSGB was modified with 3‐methacryloxypropyltrimethoxy silane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…It is worth to found that the loading of CGFSGB‐S3 into the ABS can best enhance the ABS matrix especially in the case of high filler concentrations, and the composite with CGFSGB‐S3 at a filler concentration of 8.34 wt % leads to the highest tensile strength value for the composite systems. The key reason should be that the interfacial adhesion strength between the CGFSGB‐S3 particles and the ABS matrix is considerably good in this case, and the interface may transfer effectively somewhat tensile load, resulting in the tensile strength value changing slightly with increasing the CGFSGB‐S3 weight fractions . This indicates that the interfacial adhesion strength between the CGFSGB and the ABS matrix increases because CGFSGB‐S3 had a smaller particle size distribution after the pneumatic separation.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…It is worth to found that the loading of CGFSGB‐S3 into the ABS can best enhance the ABS matrix especially in the case of high filler concentrations, and the composite with CGFSGB‐S3 at a filler concentration of 8.34 wt % leads to the highest tensile strength value for the composite systems. The key reason should be that the interfacial adhesion strength between the CGFSGB‐S3 particles and the ABS matrix is considerably good in this case, and the interface may transfer effectively somewhat tensile load, resulting in the tensile strength value changing slightly with increasing the CGFSGB‐S3 weight fractions . This indicates that the interfacial adhesion strength between the CGFSGB and the ABS matrix increases because CGFSGB‐S3 had a smaller particle size distribution after the pneumatic separation.…”
Section: Resultsmentioning
confidence: 97%
“…In this research, the CaCO 3 was used as the contrast filler. Compared with CGFSGB, the CaCO 3 has the sharp edges and corners . Therefore, the CaCO 3 may cut off the macromolecular chains of the polymer compared to the spherical CGFSGB.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations